Insilico Analysis of Codon 131 Polymorphism in FcγRIIA Gene and it is Association with Clinical Symptoms Persistence of Dengue Patients - Enny Nugraheni; Dwi Ramadhani; Mardhatillah Sariyanti; Ety Febrianti (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background. Dengue Hemorrhagic Fever (DHF) is infection caused by Dengue Virus. Failure of vascularization is a main symptom of Dengue Hemorrhagic Fever inducing mediator secretion by an immune cell. FcgRIIA and CCL2 have a significant role in dengue pathogenesis and possibility in having a chance to cause dengue with a worse manifestation. Objective. Analysis of bio-informatic structure, function and expression of FcgRIIA gene. Methods. Insilico analysis used NCBI database to find position and sequences. Analysis mutant use SNO and OMIM. Protein prediction withUniprot. Result. FcgRIIA human with access number of NM_001136219 by a length of 2429 bp has its full name as Fc Fragment of IgG receptor IIa, located in 1q23.3 chromosom. analyzed mutation was rs1801274 with type of missense protein residue function experiencing a change from Histidin (H) turning into Arginin (R) with allele of wild-type A and becoming G amino acid position of 166. there was structural difference of FcgRIIA gene in wild type and mutant. Conclusion. Gene FcγRIIA is a play a role of pathogenesis of dengue infection. Mutation in FcγRIIA have polymorfisme at Dengue Hemorrage Fever